Primer informe de un coral acropórido, Acropora valida (Dana, 1984) (Scleractina: Astrocoeniida: Acroporidae) para el Pacífico americano - Prahl, Henry von (1985)
The coral genus Acropora is reported for the first time for the Eastern Pacific. Acropora valida (Dana, 1846) previously known from the Inddo-Pacific region was collected in Gorgona Island, Colombia. A detailed description is presented, including coloration and distribution. The zoogeography of this species is discussed.